Neural Correlates of Orthographic Access in Mandarin Chinese Writing: An fMRI Study of the Word-Frequency Effect - Yang, Yang; Zhang, Jun; Meng, Ze-Long; Qin, Li; Liu, Yu-Fei; Bi, Hong-Yan (Frontiers in Behavioral Neuroscience, 2018)
Writing is an essential tool for human communication that involves multiple linguistic, cognitive and motor processes. Chinese is a logographic writing system that remarkably differs from alphabetic languages, and the neural substrates of Chinese writing is largely unknown. Using fMRI in a copying task, this study examined the neural underpinnings of orthographic access for Chinese writing by using word effect frequency as a probe. The results showed that writing low-frequency Chinese characters evoked greater activation in the bilateral superior/middle/inferior frontal gyrus, inferior/superior parietal lobule and fusiform gyrus than writing high-frequency characters, suggesting the brain regions required by orthographic access in Chinese writing. Moreover, functional connectivity analysis further demonstrated that word frequency effect modulated the neural connections between the bilateral fusiform gyrus and the connections within the frontal-occipital networks and the parietal-occipital networks, indicating the visual-orthographic, visual-motor and phonological routes that were involved in orthographic access for Chinese writing. Together, these findings for the first time illustrated the neural basis of orthographic access necessary for written production of Chinese, shedding new light on the cognitive architecture of writing in various writing systems.